2020
DOI: 10.48550/arxiv.2004.02534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weakly and Strongly Aperiodic Subshifts of Finite Type on Baumslag-Solitar Groups

Abstract: We study the periodicity of subshifts of finite type (SFT) on Baumslag-Solitar groups. We show that for residually finite Baumslag-Solitar groups there exist both strongly and weakly-but-not-strongly aperiodic SFTs. In particular, this shows that unlike Z 2 , but as Z 3 , the notions of strong and weak periodicity are different for residually finite BS groups. More precisely, we prove that the weakly aperiodic SFT on BS(m, n) presented by Aubrun and Kari [3] is in fact strongly aperiodic on BS(1, n). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In [3] Aubrun and Kari constructed SFTs on BS(1, n) groups, which were shown to be SA by Esnay and Moutot in [16]. Furthermore, in a recent paper Aubrun and Kari [4] showed that the Domino Problem is undecidable for all BS(m, n).…”
Section: Other Geometriesmentioning
confidence: 98%
“…In [3] Aubrun and Kari constructed SFTs on BS(1, n) groups, which were shown to be SA by Esnay and Moutot in [16]. Furthermore, in a recent paper Aubrun and Kari [4] showed that the Domino Problem is undecidable for all BS(m, n).…”
Section: Other Geometriesmentioning
confidence: 98%
“…These notions are equivalent for Z 2 , but differ in general: On Z 3 , one can build weakly-but-not-strongly aperiodic tilesets easily from strongly aperiodic tilesets of Z 2 , they exist on all Baumslag-Solitar groups which are not virtually abelian [3,11], and Cohen constructs one for the lamplighter group in [8]. On Z 3 and (at least) amenable Baumslag-Solitar groups, also strongly aperiodic tilesets exist, while on L none are known.…”
Section: Introductionmentioning
confidence: 99%
“…These groups were first introduced (though their origin might be older) in [BS62] by G. Baumslag and D. Solitar, in order to provide an example of a non-Hopfian group with two generators and one relator, namely, one which is isomorphic to one of its (proper) quotient groups. Since then these groups have gained attention in the fields of combinatorial group theory and geometric group theory as examples and counterexamples of different properties [Har03,Mes72], and more recently in the field of symbolic dynamics [AK13, CFKP16,EM20].…”
Section: Introductionmentioning
confidence: 99%